KOMUNIKASI INTERPERSONAL GURU DALAM MENYAMPAIKAN PESAN DAKWAH KEPADA SISWA SMP TUNAGRAHITADI SLB SABILILLAH CUKIR DIWEK JOMBANG - Candra Kusumawati; Moh. Slamet (Spektra Komunika : Jurnal Komunikasi & Dakwah, 2024)
This research explores the use of interpersonal communication in delivering religious messages to children with special needs, particularly those with intellectual disabilities, at SLB Sabilillah. Children with special needs face unique challenges that require sensitive and effective communication approaches. In this context, teachers utilize verbal interpersonal communication to deliver religious teachings based on Islamic principles in line with the Quran and Hadith. A qualitative approach is employed in this study, with a case study as the research method. Data is obtained through observation, interviews, and documentation, and verified using triangulation techniques. The aim of this research is to describe the types of interpersonal communication used by teachers in delivering religious messages to middle school students at SLB Sabilillah. Thus, this study provides insights into communication practices in the context of inclusive education for children with special needs.